2007
DOI: 10.1039/b704864e
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic resonances in microfluidic chips: full-image micro-PIV experiments and numerical simulations

Abstract: We show that full-image micro-PIV analysis in combination with images of transient particle motion is a powerful tool for experimental studies of acoustic radiation forces and acoustic streaming in microfluidic chambers under piezo-actuation in the MHz range. The measured steady-state motion of both large 5 microm and small 1 microm particles can be understood in terms of the acoustic eigenmodes or standing ultra-sound waves in the given experimental microsystems. This interpretation is supported by numerical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
118
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 24 publications
7
118
0
Order By: Relevance
“…We can also neglect the influence from the Stokes drag due to the acoustic streaming. This was demonstrated experimentally by Hags€ ater et al 32 In a direct comparison of the acoustic forces on microbeads in a microfluidic chamber it was shown that the motion of 1 mm beads was governed entirely by Stokes drag from the acoustic streaming, while the motion of the 5 mm beads was dominated by the acoustic radiation force. Moreover, in this work we never observed any traces of acoustic flow rolls.…”
Section: Transverse Particle Pathmentioning
confidence: 79%
“…We can also neglect the influence from the Stokes drag due to the acoustic streaming. This was demonstrated experimentally by Hags€ ater et al 32 In a direct comparison of the acoustic forces on microbeads in a microfluidic chamber it was shown that the motion of 1 mm beads was governed entirely by Stokes drag from the acoustic streaming, while the motion of the 5 mm beads was dominated by the acoustic radiation force. Moreover, in this work we never observed any traces of acoustic flow rolls.…”
Section: Transverse Particle Pathmentioning
confidence: 79%
“…43 This is mainly due (i) to the fact that the acoustic primary radiation force scales with particle's volume, 45 and (ii) to the increased particle susceptibility with respect to hydrodynamic drag forces resulting from acoustic streaming or thermal convection. 52,53 It has been found that at diameters of around 1 μm there is a transition to drag-dominated behaviour for operating frequencies of ~2 MHz. 52,54 For these reasons, few studies have demonstrated acoustofluidic concentration of flowing particles with diameter <2 μm 49,55 (Table I).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, acoustic streaming and acoustophoretic motion of microparticles in acoustofludic devices have been measured using various methods, most notably micro particle image velocimetry (μPIV) and particle tracking velocimetry (PTV). Experimental investigations have shown that μPIV [11][12][13] and PTV 14,15 are powerful tools for analysing 2D microchannel acoustophoresis. Fully 3D particle tracking has been demonstrated using μPIV with depth of correlations 16 and astigmatism particle tracking velocimetry [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%